Safety, equity and monitoring: a review of the gaps in maternal vaccination strategies for Aboriginal and Torres Strait Islander women. Issue 2 (1st February 2020) - McHugh, Lisa; Crooks, Kristy; Creighton, Amy; Binks, Michael; Andrews, Ross M
ABSTRACT: Influenza and pertussis infections are disproportionately higher among Aboriginal and Torres Strait Islander women and their infants compared to other Australians. These infections are potentially preventable through vaccination in pregnancy; however, there is a lack of systematic monitoring and therefore knowledge of vaccine uptake, safety and effectiveness in Australia, and specifically among Aboriginal and Torres Strait Islander women. The limited data available suggest there is a lower uptake of maternal vaccination among Aboriginal and Torres Strait Islander women compared to non-Aboriginal and Torres Strait Islander women, and this review seeks to explore potential reasons and the knowledge gaps in this regard. Other key gaps include the equitable access to quality antenatal care for Aboriginal and Torres Strait Islander women; and pregnancy loss <20 weeks gestation. Furthermore, our review highlights the importance of addressing these gaps in maternal vaccination strategies in partnership with Aboriginal and Torres Strait Islander peoples.